Between a rock and a hard place: The burdens of uncontrolled fire for smallholders across the tropics. (September 2021) - Carmenta, Rachel; Cammelli, Federico; Dressler, Wolfram; Verbicaro, Camila; Zaehringer, Julie G.
Highlights: Smallholders navigate a context of risk created by landscape flammability, burden and prohibitive policy to practice swidden. Place-based burdens of uncontrolled fires are 'invisible' from the mainstream discourse yet are significant. Recovering from, and mitigating uncontrolled fires falls largely to local land managers, extenuating existing vulnerabilities. Recognizing place-based burdens- subjective, objective and relational, is critical to developing equitable resilience. Distinguishing diverse fire types, users and landscape contexts could provide a platform to develop more just fire policy. Abstract: Once fire-resistant rainforests are becoming fire prone. Uncontrolled fires reflect new ecologies of the Anthropocene, driven by interactions of multiple actors and sectors across scales. They threaten the ecological integrity of tropical forests, impact global climate regimes and importantly cause considerable social and economic burdens. Numerous smallholder farming communities throughout the forested tropics experience the immediate place-based damages of uncontrolled fires and increasingly flammable landscapes. However, these burdens remain largely 'invisible' as leading narratives concentrate on losses accrued at aggregate scales, including to climate and biodiversity. Rather, smallholder farmers are often cast as culprits of contagion rooted in colonial condemnation of their customary fire-based agricultural practices. We use an environmental justice lens, notably the dimensions of recognition and distribution, to reveal the distributional burdens of uncontrolled fires for these land managers. We use empirical data from four case studies in three countries: Brazil, Madagascar and the Philippines, to explore the i) burdens of uncontrolled fire, ii) changing risks, iii) drivers and iv) responses to uncontrolled fire, and finally, the v) level of smallholder dependence on intentional fire. We show that place-based burdens of uncontrolled landscape fire are significant, including in landscapes where fire frequency is low. Burdens are both material and non-material and include infringements on food security, health, livelihoods, social relations and the burden of prohibitive fire policy itself. Equitable responses to uncontrolled fires must be sensitive to the distinctions between fire types. Further, we suggest that through bringing visibility to the place-based burdens of uncontrolled fires, we can begin to co-design resilient responses that avoid placing the final burden of risk reduction on to marginalized smallholder farming communities.